Projected Sea Surface Temperature Pattern Change and Madden‐Julian Oscillation Activity in a Warmer Climate - Amanda F. M. Bowden; Eric D. Maloney (Geophysical Research Letters, 2025)
Abstract The Madden Julian Oscillation (MJO) consists of a tropical convective region that propagates eastward through the Indo‐Pacific warm pool. Decadal climate variability alters sea surface temperature patterns, affecting the MJO's basic state. This investigation examines the impact of projected SST and moisture pattern changes over the 21st Century on MJO precipitation and zonal wind amplitude changes in 80 members of the Community Earth System Model 2 Large Ensemble in the SSP370 radiative forcing scenario, each with its unique representation of decadal variability. Ensemble members with strongest MJO precipitation change in a given 20‐year period have a more El Niño‐like east Pacific warming pattern. MJO amplitude increases for east Pacific warming because of a strengthened meridional moisture gradient that supports MJO eastward propagation. A stronger vertical moisture gradient also exists for ensemble members with preferential east Pacific warming, which supports a stronger MJO under moisture mode theory.